2016
DOI: 10.21037/jtd.2016.03.49
|View full text |Cite
|
Sign up to set email alerts
|

Younger women have a better prognosis among patients with esophageal squamous cell carcinoma after esophagectomy

Abstract: Among patients with ESCC after esophagectomy, women younger than age 55 years attained a favorable prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…In addition, we explored the age-dependent relationship between sex and EC survival. Several previous studies have suggested that intrinsic biological sex hormones could be an underlying mechanism that explains the female advantage in cancer incidence and morbidity ( 6 , 8 , 9 , 14 , 22 ). Age 46–55 years is generally used as a surrogate for the perimenopausal period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we explored the age-dependent relationship between sex and EC survival. Several previous studies have suggested that intrinsic biological sex hormones could be an underlying mechanism that explains the female advantage in cancer incidence and morbidity ( 6 , 8 , 9 , 14 , 22 ). Age 46–55 years is generally used as a surrogate for the perimenopausal period.…”
Section: Discussionmentioning
confidence: 99%
“…However, sex-based disparities in cancer survival are sustained after adjusting for these known risk factors in many cases. In many studies, 55 years of age was generally used as a cut-off age to enter menopause because age is linked to changes in estrogen levels in the life cycle of females ( 5 , 6 ). Mathieu et al found that the annual percentage change in esophageal adenocarcinoma incidence rates for female patients during the same period was negatively correlated with ages 50–54 years and 60–64 years ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some investigations also suggested that women with ESCC have a favorable prognosis. Su et al analyzed the prognosis of 674 ESCC patients who underwent surgical resection and found that the 5-year survival rate for females was much higher than that for males (46.8% vs 36.7%, p =0.003) 41. Morita et al .…”
Section: Discussionmentioning
confidence: 99%
“…Female sex has been reported to have a better prognosis with esophageal carcinoma. [222324] The influence of younger age and hormones such as estrogen and androgen determine a role in better survival among female patients. [2324]…”
Section: Discussionmentioning
confidence: 99%